Interpretasi Surah Al-Baqarah Ayat 234 Tentang Iddah Perempuan yang Meninggal Suaminya: Pendekatan Tafsir Ahkam dan Psikologi - Lailatul Rif'ah; Lailatul Mas’udah (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This study examines the concept of ʿiddah for women whose husbands have passed away based on Qur’anic exegesis of QS. al-Baqarah [2]: 234 by integrating the perspectives of tafsīr aḥkām and grief psychology. Employing a qualitative library research design, the study analyzes classical and contemporary Qur’anic commentaries alongside relevant psychological theories on bereavement. The findings indicate that the prescribed ʿiddah period of four months and ten days constitutes a binding legal injunction aimed at safeguarding lineage, preserving women’s dignity, and honoring the sanctity of marriage. However, various social restrictions imposed on women during ʿiddah in contemporary practice are not entirely grounded in the Qur’anic text but are largely shaped by cultural constructions and historical interpretations. From a psychological perspective, ʿiddah functions as a transitional phase that facilitates emotional adjustment, identity reconstruction, and psychological stabilization following spousal loss. This study argues that ʿiddah should be understood as a holistic Qur’anic injunction encompassing legal, social, and psychological dimensions, and thus requires contextual interpretation to ensure a more just, humane, and relevant application in the lives of contemporary Muslim women.